Sociocultural Approach to Learning and Teaching Art and Visual Culture: Medieval Heritage in the Context of Modern Visual Culture - Subotić Krasojević, Iva N. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The subject of the paper is a sociocultural approach to a teaching/learning process, regarding contemporary context of the situation in which that process is happening. The first segment of the paper is based on theoretical sociocultural approach to learning, especially CHAT (Cultural Historical Activities Theory). It emphasizes a role of culture in education, and shows learning as a meaning making process, which depends on all of its participators and the context. Second part is devoted to a process of teaching and learning art and visual culture. Case study shows an example of sociocultural approach to the medieval heritage. According to a school knowledge of our high school students, the key ideas of medieval period are based on power of church and religious wars. But, according to their activities in contemporary visual culture (games, films, series, comic books, LARP) these ideas become more magical than dark. They are interested in such themes of visual culture as dragons, weapons, knights, chivalry code, and fantastic beings. This paper intends to fill the gap between scientific historical approach of the curriculum and textbooks and students' experiences of visual and popular culture. The approach is based on methodologies of humanistic sciences that research medieval heritage in context of pop-cultural contents, as well as the context of history of private lives and wide visual culture. Having in mind the postulates of contemporary teaching and learning that depend on the context, the aim of the paper is searching for the teaching methods that will lead to cooperative interpretation and understanding of different cultures.
Keywords: sociocultural approach to learning; medieval heritage; visual culture; context; teaching methods